Protagonismo e autonomia na Política Nacional de Assistência Social /PNAS e no Sistema Único da Assistência Social/SUAS : reflexões necessárias - Viana, Roberta Rangel (2014)
The objective of the research is to analyze the theoretical perspectives that guide the concepts of autonomy and leadership in the National Social Assistance Policy (2004) and Basic Operational Norm of the Unified Social Assistance System (2005). Therefore, it starts from the assumption that in the struggle for the consolidation assistance as a social right are present conflicting views and advocates political forces of different positions. Thus sought to identify the influence of the academic debate on social service assistance, the decisions of the Federal Council and Regional Social Service and the World Bank guidelines for social policies in Latin America. The research was documentary character. The data collection occurred from the scholarship on social assistance in the period, records of the National Council of Social Assistance and reports provided by the World Bank website. For data analysis we used the technique of content analysis. It was identified that there was no specific discussion of autonomy and leadership in the process of reworking the National Policy on Service and that the final text of the documents express autonomy and leadership now in social control perspective, sometimes linked to the potential development perspective and skills of individuals and families. The survey results reveal a conceptual imprecision that contributes to an approximation of the concepts to liberal theory disseminated by the World Bank to develop public policies aimed at providing individuals and families skills and capabilities for self-protection. It was concluded that autonomy and leadership despite arise in the social service debate as a break with subordinates practices are characterized in the National Social Assistance Policy (2004) and Basic Operational Norm of the Unified Social Assistance System (2005) as the final product accountability process one of the families and individuals for the overcoming.